Improvement of the solution search method based on the cuckoo algorithm - Mohammed, Basem Abdullah; Zhuk, Oleksandr; Vozniak, Roman; Borysov, Ihor; Petrozhalko, Volodymyr; Davydov, Igor; Borysov, Oleh; Yefymenko, Oleksandr; Protas, Nadiia; Kashkevich, Svitlana (Eastern-European journal of enterprise technologies, 2023)
An improved method of finding solutions based on the cuckoo algorithm is proposed. The research object is the decision-making support systems. The research subject is the decision making process in management tasks using artificial intelligence methods. The hypothesis of the research is to increase the efficiency of decision making with a given assessment reliability. The proposed method is based on a combination of the cuckoo algorithm and evolving artificial neural networks. The method has the following differences: ‒ an additional processing of the source data takes place taking into account the uncertainty about the state of the control objects and the type of data noise about the state of the control object is additionally taken into account; ‒ the state model of the control object is adjusted taking into account the available computing resources of the system; ‒ added procedures to reduce the probability of detecting nests and reducing the length of the cuckoo’s step; ‒ knowledge bases about management objects are additionally taught. The training procedure consists in learning the synaptic weights of the artificial neural network, the type and parameters of the membership function and the architecture of individual elements and the architecture of the artificial neural network as a whole. The effectiveness of the proposed method was evaluated and it was established that the proposed modification provides a better value of the objective function compared to the results obtained by other authors and ensures the fulfillment of all restrictions. The specified example showed an increase in the efficiency of data processing at the level of 21–28 % due to the use of additional improved procedures. It is advisable to use the proposed method in decision making support systems of automated control systems. Запропоновано удосконалену методику пошуку рішень на основі алгоритму зозулі. Об’єктом дослідження є системи підтримки прийняття рішень. Предметом дослідження є процес прийняття рішення в задачах управління за допомогою методів штучного інтелекту. Гіпотезою дослідження є підвищення оперативності прийняття рішення при заданій достовірності оцінювання. Запропонована методика заснована на поєднанні алгоритму зозулі та штучних нейронних мереж, що еволюціонують. Методика має наступні відмінності: ‒ додатково відбувається оброблення вихідних даних з урахуванням невизначеності про стан об’єктів управління та додатково враховується тип зашумленості даних про стан об’єкту управління; ‒ здійснюється коригування моделі стану об’єкту управління з урахуванням наявних обчислювальних ресурсів системи; ‒ додані процедури зменшення ймовірності виявлення гнізд та зменшення довжини кроку зозулі; ‒ додатково відбувається навчання баз знань про об’єкти управління. Процедура навчання полягає в тому, що відбувається навчання синаптичних ваг штучної нейронної мережі, типу та параметрів функції належності, а також архітектури окремих елементів і архітектури штучної нейронної мережі в цілому. Проведено оцінку ефективності запропонованої методики і встановлено, що запропонована модифікація забезпечують краще значення цільової функції порівняно з результатами, отриманими іншими авторами та забезпечує виконання всіх обмежень. Зазначений приклад показав підвищення ефективності оперативності обробки даних на рівні 21–28 % за рахунок використання додаткових удосконалених процедур. Запропоновану методику доцільно використовувати в системах підтримки прийняття рішень автоматизованих системах управління